2014
DOI: 10.5194/nhess-14-1071-2014
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble study of HyMeX IOP6 and IOP7a: sensitivity to physical and initial and boundary condition uncertainties

Abstract: Abstract. The first Special Observation Period of the HyMeX campaign took place in the Mediterranean betweenSeptember and November 2012 with the aim of better understanding the mechanisms which lead to heavy precipitation events (HPEs) in the region during the autumn months. Two such events, referred to as Intensive Observation Period 6 (IOP6) and Intensive Observation Period 7a (IOP7a), occurred respectively on 24 and 26 September over southeastern France. IOP6 was characterised by moderate to weak low-level … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 41 publications
(54 reference statements)
3
36
0
Order By: Relevance
“…[] and Hally et al . [, ] who demonstrated that the sensitivity of heavy precipitation simulations to physical perturbations is dependent on the model skill and larger‐scale conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[] and Hally et al . [, ] who demonstrated that the sensitivity of heavy precipitation simulations to physical perturbations is dependent on the model skill and larger‐scale conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The large variability in the amount, location, and pattern of rainfall suggests that a 24 h precipitation forecast could be sensitive to IC uncertainties with synoptic conditions favorable for heavy precipitation over central Eastern China during the Meiyu season. This finding is in agreement with the results of Bei and Zhang [] and is consistent with recent studies of heavy precipitation events over the Mediterranean basin in autumn [ Hally et al ., , ].…”
Section: Sensitivity To Initial Conditionsmentioning
confidence: 98%
“…Tapiador et al, 2012). Also, Hally et al (2013) concluded for heavy precipitation events that the level of sensitivity to physics perturbations compared to initial/boundary conditions is case dependent.…”
Section: Introductionmentioning
confidence: 95%
“…From another point of view, in Hally et al . (), IOPs 6 and 7a that occurred over southeastern France are described.…”
Section: Results For Individual Periodsmentioning
confidence: 99%